2021
DOI: 10.3390/cancers13215289
|View full text |Cite
|
Sign up to set email alerts
|

CSF1R Inhibition Combined with GM-CSF Reprograms Macrophages and Disrupts Protumoral Interplays with AML Cells

Abstract: Relapse is a major issue in acute myeloid leukemia (AML) and while the contribution of gene mutations in developing drug resistance is well established, little is known on the role of macrophages (MΦs) in an AML cell microenvironment. We examined whether myeloblasts could educate MΦs to adopt a protumoral orientation supporting myeloblast survival and resistance to therapy. Flow cytometry analyses demonstrated that M2-like CD163+ MΦs are abundantly present, at diagnosis, in the bone marrow of AML patients. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 93 publications
0
17
0
Order By: Relevance
“…These effects were found to be dependent on arginase II activity, as the administration of inducible nitric oxide synthase (iNOS) inhibitors (NOHA and L-NMMA) or exogenous arginine significantly attenuated CD206 expression in co-cultured macrophages while restoring T-cell proliferation (56). Collectively, these findings confirm the capacity of AML blasts to generate an immunosuppressive microenvironment within the BM and PB, thereby promoting their own survival (53, 56,61).…”
Section: Acute Myeloid Leukemiamentioning
confidence: 72%
See 2 more Smart Citations
“…These effects were found to be dependent on arginase II activity, as the administration of inducible nitric oxide synthase (iNOS) inhibitors (NOHA and L-NMMA) or exogenous arginine significantly attenuated CD206 expression in co-cultured macrophages while restoring T-cell proliferation (56). Collectively, these findings confirm the capacity of AML blasts to generate an immunosuppressive microenvironment within the BM and PB, thereby promoting their own survival (53, 56,61).…”
Section: Acute Myeloid Leukemiamentioning
confidence: 72%
“…Subsequent studies have confirmed that IRF7 can activate the SAPK/JNK pathway in macrophages to promote their polarization towards the M1 phenotype, thereby prolonging the survival time of leukemia mice. Several studies have also demonstrated that the utilization of a CSF1R inhibitor in combination with GM-CSF effectively induces the polarization of pro-tumor M2 macrophages towards anti-tumor M1 macrophages in the TME, thus reversing TAMs-induced tumor resistance and promoting apoptosis of myeloblasts (61,63). Moore et al initially proposed that LC3-associated phagocytosis of BM macrophages serves as a major mechanism for mediating the apoptosis of AML cells and can activate the stimulator of IFN genes (STING) pathway in macrophages, thus enhancing their phagocytic capacity and effectively suppressing AML growth (64).…”
Section: Acute Myeloid Leukemiamentioning
confidence: 99%
See 1 more Smart Citation
“…Switching M1 to M2 is through lasting exposure to polarizing molecules or direct cell-to-cell contact between macrophages and cancer cells ( 102 ). Smirnova, T. further proved that in the presence of GM-CSF, inhibiting CSF1R could repolarization macrophage, thus improving the efficiency of AML therapy, which indicated a promising therapeutic method to modulate macrophage phenotype ( 103 ).…”
Section: Macrophages In Leukemiamentioning
confidence: 99%
“…In addition, M2 macrophages are less effective for tissue repair in these chronic inflammatory conditions. , Therefore, in this context, promoting M2 macrophage polarization and/or inhibiting M1 macrophage differentiation may enhance healing. In contrast, anti-inflammatory M2 macrophages support tumor growth and metastasis. ,, Tumor-associated macrophages (TAMs) share many common features with M2 macrophages, leading to suppression of anti-tumor immune reactivity, one of the current limitations of cancer therapies. ,, Hence, suppressing M2 and elevating M1 macrophage polarization may improve treatment outcomes for various diseases or injuries.…”
Section: Introductionmentioning
confidence: 99%